Concurrent Growth and Formation of Electrically Contacted Monolayer Transition Metal Dichalcogenides on Bulk Metallic Patterns. Issue 4 (20th October 2016) - Khadka, Sudiksha; Lindquist, Miles; Aleithan, Shrouq H.; Blumer, Ari N.; Wickramasinghe, Thushan E.; Kordesch, Martin E.; Stinaff, Eric
Abstract : A process for the growth of self‐contacting monolayers to bulk metallic contacts is reported. Monolayer films, grown on and around patterns of bulk transition metals using chemical vapor deposition, display strong luminescence, monolayer Raman signatures, and relatively large crystal domains, while the metallic patterns provide as‐grown contacts to the material, offering a path for device fabrication and large‐scale production.